Resilient Pathways of Small Island Tourism: A Qualitative Study of Post- COVID Recovery in Indonesia - Supiandi, Supiandi; Habibi, Putrawan (Advances in Tourism Studies, 2024)
This study explores how tourism communities in Indonesia navigated disruption and recovery in the aftermath of the COVID-19 pandemic. Using a qualitative case study approach, data were collected through semi-structured interviews, focus group discussions, and participant observation across selected small island destinations. Thematic analysis revealed that the pandemic not only disrupted livelihoods but also reshaped perceptions of vulnerability and resilience. Respondents emphasized the severity of income loss, psychological distress, and the erosion of community ties during the crisis. However, recovery pathways were marked by adaptive strategies including diversification into agriculture and fisheries, increased reliance on domestic tourists, and the creative use of digital platforms for marketing and communication. Community solidarity, traditional knowledge, and cultural practices emerged as critical resources that supported both economic survival and social cohesion. The findings highlight that resilience in Indonesian tourism is constructed through a combination of adaptive innovation and socio-cultural embeddedness rather than through technical or policy frameworks alone. This study contributes to resilience theory by grounding it in the lived experiences of local stakeholders and offers practical insights for policymakers seeking to support sustainable and inclusive tourism recovery in post-crisis contexts.